Application of chromatographic and spectroscopic-based methods for analysis of omega-3 (ω-3 FAs) and omega-6 (ω-6 FAs) fatty acids in marine natural products - Rohman, Abdul; Irnawati, Irnawati; Windarsih, Anjar; Riswanto, Florentinus Dika Octa; Indrayanto, Gunawan; Riyanto, Sugeng; Ahmad Fadzillah, Nurrulhidayah; Abu Bakar, Nor Kartini (MDPI, 2023)
Abstract: Omega-3 fatty acids v(ω-3 FAs) such as EPA (eicosapentaenoic acid) and DHA (docosahexaenoic acid) and omega-6 fatty acids (ω-6 FAs) such as linoleic acid and arachidonic acid are important fatty acids responsible for positive effects on human health. The main sources of ω-3 FAs and ω-6 FAs are marine-based products, especially fish oils. Some food, supplements, and pharmaceutical products would include fish oils as a source of ω-3 FAs and ω-6 FAs; therefore, the quality assurance of these products is highly required. Some analytical methods mainly based on spectroscopic and chromatographic techniques have been reported. Molecular spectroscopy such as Infrared and Raman parallel to chemometrics has been successfully applied for quantitative analysis of individual and total ω-3 FAs and ω-6 FAs. This spectroscopic technique is typically applied as the alternative method to official methods applying chromatographic methods. Due to the capability to provide the separation of ω-3 FAs and ω-6 FAs from other components in the products, gas and liquid chromatography along with sophisticated detectors such as mass spectrometers are ideal analytical methods offering sensitive and specific results that are suitable for routine quality control.